Acquired methemoglobinemia in children presenting to Italian pediatric emergency departments: a multicenter report. (3rd August 2022) - Raucci, Umberto; Stanco, Michela; Roversi, Marco; Ponticiello, Eduardo; Pisani, Mara; Rosa, Margherita; Falsaperla, Raffaele; Pavone, Piero; Bondone, Claudia; Raffaldi, Irene; Calistri, Lucia; Masi, Stefano; et al.
Abstract: Introduction: Methemoglobinemia (MetHb) is a rare inherited or acquired cause of cyanosis in children. Owing to its rarity, case reports and case series are mostly available in the current literature. This study reports data on a large sample of children with acquired MetHb. Methods: Data on patients admitted for acquired MetHb between January 2007 to December 2020 was extracted from the databases of five Italian pediatric emergency departments (EDs). Demographical and clinical characteristics was reported and discussed. Results: Nineteen cases of acquired MetHb were evaluated. Ten patients (52.6%) were male and 9 (47.4%) were female. The median age was 8.23 months. The median time from trigger to symptom onset was 6 hours. Mostly, the intoxication presumptively occurred by home ingestion of contaminated food, mainly badly preserved vegetable broth. All patients were cyanotic at admission, most patients also presented tachycardia and/or tachypnea, and two patients were comatose. Antidotal therapy with methylene blue was given in 14 patients (73.7%). The median hospital stay was 2 days. All patients survived. Discussion: As MetHb leads to the pathognomonic brown blood discoloration, blood gas analysis is mandatory immediately upon hospital arrival of a cyanotic patient. A correct medical history is crucial to identify the trigger and remove it. In our sample, the age onset was much lower than in the previous literature, and MetHb mainly due to ingestion of contaminated vegetable broth. Methylene blue led to a rapid recovery in all patients. Oxygen therapy may well lead to complete recovery when methemoglobin levels do not exceed 30% in asymptomatic and 20% in mildly symptomatic patients. Conclusions: The diagnosis and management of acquired MetHb in the emergency setting requires acknowledgment of this condition as a cause of cyanosis in the weaning child. Indeed, when promptly recognized and treated, this severe condition rapidly resolves with no significant acute sequelae.